Metabolome and transcriptome analysis reveal the pigments biosynthesis pathways in different color fruit peels of Clausena lansium L. Skeels - Zhichang Zhao; Mark Owusu Adjei; Ruixiong Luo; Huaping Yu; Yali Pang; Jian Wang; Yu Zhang; Jun Ma; Aiping Gao (Frontiers in Plant Science)
IntroductionThe color of Clausena lansium L. Skeels cv. Jixin fruit peel is brown (BP), while the mutant cv. Zijin had purple fruit peels (PP). The coloration of the peels was attributed to significant differences in chlorophyll, carotenoid, and anthocyanin content between BP and PP.MethodsThis study investigates the biosynthetic metabolic activities in the brown and purple peels of Clausena lansium L. Skeels using metabolomics and transcriptomics. It aims to identify metabolic pathways and differentially expressed genes related to flavonoids and anthocyanins biosynthesis.ResultsThe PP (purple peel) has higher levels of a-carotene and b-carotene but lower levels of chlorophyll a, chlorophyll b, and lutein compared to BP. Zeaxanthin was absent from both peels, suggesting that the b-carotene hydroxylase enzyme is not active. Both peels contain delphinidin-based (Dp) and cyanidin-based (Cy) anthocyanins, but not pelargonidin-based (Pg). The total anthocyanin content and the Dp/Cy ratio are higher in PP than in BP. The delphinidin, cyanidin, and mallow derivatives in the PP were significantly higher than in the BP. The increase of total anthocyanin content and Dp/Cy ratio may be the main reason for the peel color changing from brown to purple. The significant increase of F3H expression in purple peels suggested a higher efficiency of catalyzing the conversion of naringenin into dihydroflavonols in the PP, leading to the higher content of total anthocyanin. Despite the significant increase of FLS expression in PP, the contents of kaempferol, quercetin, and myricetin significantly decreased, suggesting that the increase of FLS expression did not lead to an increase in flavonol biosynthesis.DiscussionThe competition between F3’H and F3’5’H may determine the ratio of Dp/Cy, the higher levels of F3’H, F3’5’H, and UFGT expression, lead to the increase accumulation of total anthocyanin and Dp/Cy in PP. The deficiency of Pg in both peels resulted from the substrate specificity of the DFR enzyme. The research also describes the transition in color from BP to PP and details of the biosynthetic pathways for carotenoids and anthocyanins, elucidating the molecular processes underlying anthocyanin production.